Информационно-телекоммуникационная система поддержки принятия решений диспетчерским персоналом электрэнергетической системы; Информационные и математические технологии в науке и управлении; Ч. 1 - Боровиков Ю. С. Юрий Сергеевич (2015, 2015)
An analytical review of existing information and telecommunication systems of support of decision-making control personnel of electric power systems (its CPD DPAS). The analysis of possible areas of research in the development of its CPD DPAS. As a key component of its CPD DPAS allocated dynamic simulation of electric power systems. Theoretically, the choice, as a major, complex (hybrid)approach to the creation of its CPD DPAS that allows you to develop and implement for each significant aspect of the problem of establishing such a system are the most effective methods, ways and means, the aggregation of which ensures its successful solution in General. In line with this approach, proposed and considered two possible ways of constructing its CPD DPAS.